Biochemical response to substrate reduction therapy versus enzyme replacement therapy in Gaucher disease type 1 patients - Smid, Bouwien E. (Orphanet J Rare Dis, 2016)
BACKGROUND: We retrospectively compared biochemical responses in type 1 Gaucher disease patients to treatment with glycosphingolipid synthesis inhibitors miglustat and eliglustat and ERT. METHODS: Seventeen GD1 patients were included (n = 6 eliglustat, (two switched from ERT), n = 9 miglustat (seven switchers), n = 4 ERT (median dose 60U/kg/m). Plasma protein markers reflecting disease burden (chitotriosidase, CCL18) and lipids reflecting substrate accumulation (glucosylsphingosine, glucosylceramide) were determined. Also, liver and spleen volumes, hemoglobin, platelets, and fat fraction were measured. RESULTS: In patients naïve to treatment, chitotriosidase, CCL18 and glucosylsphingosine decreased comparably upon eliglustat and ERT treatment, while the response to miglustat was less. After 2 years, median decrease of chitotriosidase was 89 % (range 77–98), 88 % (78–92) and 37 % (29–46) for eliglustat, ERT and miglustat naïve patients respectively; decrease of CCL18 was 73 % (63–78), 54 % (43–86), and 10 % (3–18); decrease of glucosylsphingosine was 86 % (78–93), 78 % (65–91), 48 % (46–50). Plasma glucosylceramide in eliglustat treated patients (n = 4) reached values below the normal range (n = 20 healthy controls). Biochemical markers decreased or stabilized in switchers from ERT to eliglustat (n = 2), but less in miglustat switchers (n = 7). Clinical parameters responded comparably upon eliglustat and ERT treatment. CONCLUSIONS: Our explorative study provides evidence that biochemical markers respond comparably in patients receiving eliglustat treatment and ERT, while the corresponding response to miglustat treatment is less.